Analisis Hubungan Brand Awareness, Brand Image, Dan Repurchase Intention Pada Konsumen Usia 17–25 Tahun: Studi Kasus Ekosistem Teknologi Samsung Sebagai High-Tech Brand - MH. Galang Sabilillah; Yanuar Dananjaya (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study aims to examine and analyze the influence of Entertainment, Customization, Trendiness, Interaction, and Word of Mouth on Brand Awareness, as well as the impact of these five variables on Brand Image, followed by the effect of Brand Awareness and Brand Image on Repurchase intention among consumers aged 17–25 years of Samsung as a High-Tech Brand. The research model was developed based on previous studies and tested using a quantitative method with survey data. Data were collected from respondents aged 17–25 years who had used Samsung products. The sampling technique used purposive sampling, and data were obtained through online questionnaires. A total of 209 valid responses were analyzed using multiple linear regression. The results show that Entertainment, Customization, Interaction, and Word of Mouth significantly affect Brand Awareness, while Trendiness has no significant impact. Meanwhile, Entertainment and Customization significantly influence Brand Image, while Trendiness, Interaction, and Word of Mouth do not. Furthermore, both Brand Awareness and Brand Image significantly affect Repurchase intention. These findings indicate that enhancing brand-related content and strengthening brand positioning can increase consumer intention to repurchase Samsung products.